2018
DOI: 10.1002/cne.24524
|View full text |Cite
|
Sign up to set email alerts
|

Two types of sensory proliferation patterns underlie the formation of spatially tuned olfactory receptive fields in the cockroach Periplaneta americana

Abstract: In the cockroach Periplaneta americana, to represent pheromone source in the receptive space, axon terminals of sex pheromone-receptive olfactory sensory neurons (pSNs) are topographically organized within the primary center, the macroglomerulus, according to the peripheral locations of sex pheromone-receptive single walled (sw)-B sensilla. In this study, we sought to determine when and where pSNs emerge in the nymphal antenna. We revealed two different pSN proliferation patterns that underlie the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 65 publications
1
31
0
1
Order By: Relevance
“…Although the antennae of nymphal cockroaches lack sw-B sensilla 17,27,28 , previous studies suggested that nymphal cockroaches sense sex pheromones as follows. First, the A-and B-glomeruli are formed during early development, and the volumes of these glomeruli gradually increase at every moult concomitantly with the elongation of the antennae [28][29][30] . Second, the nymphal antennae exhibit weak but reliable electroantennogram responses to sex pheromones [31][32][33] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the antennae of nymphal cockroaches lack sw-B sensilla 17,27,28 , previous studies suggested that nymphal cockroaches sense sex pheromones as follows. First, the A-and B-glomeruli are formed during early development, and the volumes of these glomeruli gradually increase at every moult concomitantly with the elongation of the antennae [28][29][30] . Second, the nymphal antennae exhibit weak but reliable electroantennogram responses to sex pheromones [31][32][33] .…”
mentioning
confidence: 99%
“…Third, later instar nymphs have PB-PNs that have dendrites in the nymphal B-glomerulus 34 . Finally, a large majority of nymphal sw-A sensilla are transformed into sw-B sensilla at the final moult, and some OSNs in the nymphal sw-A sensilla extend their axon terminals into the A-and B-glomeruli 28 . Therefore, nymphal sw-A sensilla may be able to detect sex pheromones.…”
mentioning
confidence: 99%
“…Even if not statistically significant, this observation is coherent with previous electrophysiological observations, which showed that uPNs responsive to distal pheromone stimuli respond with about 60% (Hosl 1990) or 75% (Nishino 2018) of the intensity of uPNs responsive to proximal stimuli. This effect is likely due to a decrease in sensillar density along the cockroach antenna, thus to a smaller population of responsive neurons (Hösl, 1990; Watanabe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With calcium imaging analysis, we could detect a clear response to a plume of odorant localized a few millimetres from the head, but almost no activity when the odour plume was presented to a more distal antennal section. This effect can be explained only partially by the decrease in sensillar density along the antenna from proximal to distal (Hösl, 1990; Watanabe et al, 2018). Indeed, olfactory sensilla density may explain up to 2-fold decrease in sensitivity along the antenna, but not the 5-to-10-fold signal decrease that we observed ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation